The Influence of Product Quality, Personal Sales, and Pricing on Purchase Decisions at PT Panca Niaga Jaya Lestari Kisaran - Yuni Lastri Panjaitan; Rani Beby Yohana Hutagalung; Viona Adelina Lion Master; Jhekson Sitorus; Nurmaidah Ginting (CERED Indonesia Institute, 2022)
Personal selling is a skill somebody for communicate to candidate buyer in offer something products for buyers interested for To do purchase product that. Determination price policy a business entity in set price sell from products offered PT Panca Niaga Jaya Lestari Kisaran is a private company engaged in as a food distributor light that has been operate since 2002 in the Kisaran. The research method uses a quantitative approach, the type of research used is descriptive quantitative. Data was collected by means of interviews, questionnaires and documentation studies. Analysis of the data used is multiple linear regression. Population is PT Panca consumers Niaga Jaya Lestari, totaling 88 people. Determination of the sample in the study using a saturated sample. The results showed that the quality of product, personal selling and pricing simultaneously and partially have a positive and significant effect on purchasing decisions with a coefficient of determination of 0.565 or 56.5%, while the remaining 43.5 % is influenced by other factors. The conclusion of the study is simultaneously and partially product quality, personal selling and pricing have a significant effect on purchasing decisions on products PT. Panca Niaga Jaya Lestari Kisaran